Research and Evaluation on Dynamic Response Characteristics of Various Pavement Structures. (11th March 2022) - Guo, Meng; Hou, Fujin; Zhang, Shuaixiang; Li, Xu; Li, Yunliang; Bi, Yufeng
Abstract : In order to comprehensively analyze the dynamic response of full-depth asphalt pavement under moving load, a three-dimensional model of pavement structure and dynamic load moving zone are established based on ABAQUS finite element software. Based on the time history curves of different structures, the stress-strain states at the bottom of each structural layer in different structures under moving load are analyzed. The results show that the stress, strain, and shear stress of the middle layer of full-depth pavement are smaller than those of semirigid base pavement, and rutting is closely related to the deformation of this layer. The dynamic response results of the same structure at different speeds are similar, but the increase of the maximum speed will increase the shear stress at the bottom of the layer, and the road is more prone to longitudinal crack.